Is it possible to predict the physical function of lumbar disc herniation after aquatic exercises and Kotsuban Tyousei? Functionality prediction in disc herniation - B. Oda, Shigueo; Obara, Karen; H. Santos, Eduarda; R. Munaro, Giovana; G. Marcato, Raiane; G. Miranda, Camila; B. Nampo, Daniel; A. C. Silva, Pedro; R. Cardoso, Jefferson (Manual Therapy, Posturology & Rehabilitation Journal, 2024)
Background: Aquatic exercises (AE) have gained increased popularity and are widely used to treat specific and non-specific low back pain. The Kotsuban Tyousei (KT) method, which means "pelvic adjustment", proposes passive mobilization of body segments to restore or maintain pain-free move- ment in the musculoskeletal system and reduce disability. Objective: This study aimed to assess physical function through Simulation Modeling Analysis (SMA) time series approach in indi- viduals diagnosed with lumbar disc herniation (LDH). Methods: Two participants with LDH were selected and underwent combined AE and KT treatment for 16 sessions (eight sessions of each treat- ment), over the course of eight weeks. Physical function was assessed using the Roland Morris Dis- ability Questionnaire (RMDQ). Pre and during/post-intervention measurements of the RMDQ were analyzed by SMA (autocorrelation, r and significance) and the Minimum Clinically Important Difference (MCID) was reported. Results: Participant 1 exhibited improvements in pain in func- tional tests. The SMA results were autocorrelation = 0.58, r = - 0.69, P = 0.07. The MCID was not reached, however a 46.5 % RMDQ improvement (4.1 points) was found, exceeding the minimum amount of change that can be considered important. Participant 2 presented improvements in com- munity ambulation and lower limb muscle strength. For SMA the results were autocorrelation = 0.19, r = - 0.29, P = 0.28. An 18 % RMDQ improvement (2.6 points) were reported, and at the end of the treatment, the patient did not report LBP or irradiation in the posterior region of the left thigh. Conclusion: After 16 sessions of aquatic and on land exercises, two individuals diagnosed with disc a herniation did not achieved the prediction model of physical function time series analysis, how- ever, participant 1 exhibited a significant difference in MCID.